The Effect of Reading Habit on Students’ Recount Writing Skill at State Vocational High School in Kota Serang - Fajar Erlangga (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
This research is aimed at knowing the effect of reading habit on students’ recount writing skill. This research employs a survey method with samples consisting of 42 students randomly drawn from four different classes XI of SMKN in kota Serang. The data are collected by distributing questionnaires and writing tests, are analyzed applying regression and correlation analyses. The research result shows there is a significant effect of reading habit on students’ recount writing skill, as shown by the value of sig 0.017 < 0.05 and tO 2.483. Based on the result of the research, it can be concluded that reading habit has an effect on student’s recount skill.